Classification of Science in the Ihsha' Al-'Ulum (Encyclopedia of Science) Al-Farabi (870-950 AD) - M. Rozali; Nurul Syahrani Lubis (UIN Sumatera Utara Medan, 2023)
The purpose of this writing is to find out the classification of knowledge in the Book of Ihsha' al-'Ulum Al-Farabi (870-950 AD). The study discussed how the classification of science in Al-Farabi's work. The method used is content analysis on a book written by Al-Farabi, namely Kitab Ihsha' al-'Ulum. The discussion of the book reveals that it does not state that there is a dichotomy of the sciences. Al-Farabi, only does division or classification of knowledge both ontology, epistemology and axiology. Al-Farabi, mentions various terms that are almost the same but semantically contain hierarchical meanings. The term is taqsim/aqsam or division, shinfun/ashnaf or part and juz'un/ajzaun or the smallest part. This illustrates that what al-Farabi did was collect and calculate (Ihsha') the diversity (ta'did) of knowledge in his time and then detail (tafsil) these sciences down to the smallest part so that the levels (maratib) of knowledge were known. Al-Farabi divides knowledge into two parts, namely: Theoretical Sciences (al-'Ulum al-Nadzoriyah), and Practical Sciences (al-'Ulum al-'Amaliyah wa al-Falsafatu al-Madaniyah). This division can be seen from the division of knowledge into five articles which describe these sciences into theoretical and practical terms and Practical Sciences (al-'Ulum al-'Amaliyah wa al-Falsafatu al-Madaniyah). This division can be seen from the division of knowledge into five articles which describe these sciences into theoretical and practical terms and Practical Sciences (al-'Ulum al-'Amaliyah wa al-Falsafatu al-Madaniyah). This division can be seen from the division of knowledge into five articles which describe these sciences into theoretical and practical terms.